2010
DOI: 10.1088/0022-3727/43/38/385106
|View full text |Cite
|
Sign up to set email alerts
|

Current–voltage characteristics of dendrimer light-emitting diodes

Abstract: We have investigated current-voltage (I-V) characteristics of unipolar and bipolar organic diodes that use phosphorescent dendrimers as the emissive organic layer. Through simulation of the measured I-V characteristics we were able to determine the device parameters for each device structure studied, leading to a better understanding of injection and transport behaviour in these devices. It was found that the common practice of assuming injection barriers are equal to the difference between bare electrode work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…However, later work has suggested that injection barriers may commonly exist in metal-organic interfaces that are normally assumed to be ohmic, 6 and other modeling work has reached the same conclusion. 52 This may account for the necessity of including injection barriers in the KMC model, especially as it includes an explicit hopping description between discrete energy levels, which is not included in drift-diffusion modeling.…”
Section: Resultsmentioning
confidence: 99%
“…However, later work has suggested that injection barriers may commonly exist in metal-organic interfaces that are normally assumed to be ohmic, 6 and other modeling work has reached the same conclusion. 52 This may account for the necessity of including injection barriers in the KMC model, especially as it includes an explicit hopping description between discrete energy levels, which is not included in drift-diffusion modeling.…”
Section: Resultsmentioning
confidence: 99%
“…Although much of the context for this analysis has concerned dendrimeric systems acting as solar energy harvesters, there are several other important and emerging areas of application deserving mention, including molecular sensing [104][105][106], catalysis [104,107], medical photonics [104,108] and light-emitting diodes [109][110][111]. Most uses exploit the following generic properties: the possession of a multiplicity of chromophores that are responsible for initial photon absorption, and which can also act as relays; these groups display broad and intense absorption bands, and correspondingly strong emission bands; RET mechanisms are in place for the efficient transmission of electronic excitation by a sequence of transfers, providing a means for the direct routing of each excitation from peripheral to core chromophores; irreversibility of energy capture is achieved through intramolecular relaxation (energy losses) at each intervening site.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional device models adapted from inorganic device simulation have given strong insights into OLED behavior at macroscopic length scalesVfor recent examples, see [38] and [39]Vand they have been reviewed along with the GDM in [40]. The hopping nature of conduction in organic materials discussed in Section II is taken into account by the use of field-dependent charge mobilities obtained from experiment.…”
Section: Device Modelsmentioning
confidence: 99%